Transplantation of pediatric renal allografts from donors less than 10 kg. Issue 11 (27th June 2018) - Mitrou, Nicholas; Aquil, Shahid; Dion, Marie; McAlister, Vivian; Sener, Alp; Luke, Patrick P.
Abstract : Few transplant programs use kidneys from donors with body weight (BW) < 10 kg. We hypothesized that pediatric en bloc transplants from donors with BW < 10 kg would provide similar transplant outcomes to larger grafts. All pediatric en bloc renal transplants performed at our center between 2001 and 2017 were reviewed (N = 28). Data were stratified by smaller (donor BW < 10 kg; n = 11) or larger donors (BW > 10 kg; n = 17). Renal volume was assessed during follow‐up with ultrasound. Demographic characteristics were similar between the 2 groups of recipients. After mean follow‐up of 44 months (smaller donors) and 124 months (larger donors), graft and patient outcomes were similar between groups. Serum creatinine at 1, 3, and 5 years was no different between groups. At 1 day posttransplant, mean total renal volume in the smaller donors was 28 ± 9 mm 3 vs 45 ± 12 mm 3 ( P < .01). By 3 weeks, it was 53 ± 19 mm 3 (smaller donors) versus 73 ± 19 mm 3 (larger donors) ( P = NS). Complication rates were similar between both groups with 1 case of venous thrombosis in the smaller group. With experience, outcomes are equivalent to those from larger pediatric donors. Abstract : Pediatric en bloc donors weighing less than 10 kg have similar outcomes to donors weighing more than 10 kg in renal transplant recipients.